Calibration [Air Monitoring Methods, 2016]. Issue 1 (26th January 2017) - Hebisch, R.; Ball, M.; Breuer, D.; Heckmann, P.; Krämer, W.; Maschmeier, C.‐P.; Nitz, G.; Riepe, W.; Schuh, C.; Brock, T.H.; Hartwig, A.; ,
Abstract : Workplace measurements are intended to give information about kind and extent of workers' exposure during their activities with hazardous substances. For this purpose calibration is necessary to establish the relationship between a known concentration and the corresponding measuring signal resulting in reliable measuring results at a high level of quality. Therefore, calibration strongly influences accuracy and precision of the whole measuring procedure. Calibration is required for different tasks. During development of a measurement procedure the calibration range has to be determined, for which there must be a linear relationship between the concentration of the analyte and the response of the analytical procedure. Important analytical parameters such as limit of detection (LOD) and limit of quantification (LOQ) may also be determined using calibration procedures. Normally, calibration is needed for the quantification of hazardous substances from workplace measurements. In this case the composition of calibration solutions should be as near as possible to that of the collected samples. The calibrated concentration range should yield unambiguous analytical results. Traceability of the complete calibration procedure from the measuring result back to the typically used (certified) reference material must be ensured. This chapter describes how to perform calibration for different purposes and the possible sources of errors which have to be considered. Requirements for reference materials are also specified. Joint Publication of the Analytical Subcommittee of the Chemistry Board of Experts of the Expert Committee Raw Materials and Chemical Industry of the German Social Accident Insurance and the Working Group "Air Monitoring Methods" of the Permanent Senate Commission of the DFG for the Investigation of Health Hazards of Chemical Compounds in the Work Area.